THE BANK'S EFFECT ON DIGITAL CAPABILITY AND KNOWLEDGE ACQUISITION WITHIN THE PERFORMANCE AND DIGITAL NATIVE'S PERCEPTION OF MOBILE BANKING - Aslan, Buket; Sönmez Çakır, Fatma; Adiguzel, Zafer; Çakır, Fatma Sönmez (Univ Jaen, Serv Publicaciones, 2022)
The aim of this study is to analyze the effects of digital skills and knowledge acquisition on the performance and digital natives perceptions of mobile banking as a result of the increase in the use of mobile banking applications with the spread of the internet. A survey was conducted with 337 white-collar specialists working in the general directorates of banks. The SmartPLS 3.3.3 program was used, and the obtained data were analyzed. Digital capability and knowledge acquisition have positive effects on both the performances and digital natives perceptions of mobile banking. It is supported by hypotheses that banks should give importance to digitalization and information. The research covers a specific sector within a certain field, since the data were obtained from the expert-level personnel working in the general directorates of banks in Istanbul. The results could also be applied to analyze the effective performance of other companies that provide services through mobile applications.
Keywords: Digital Capability; Knowledge Acquisition; Financial Performance; Digital Natives P.M.B.; Innovation Performance